The Effects of Internet Use in the Classroom on Reading Comprehension, Metacognitive Awareness, and Motivation - Fatemeh Mirzapour; Ahmed Azeez Mohammed (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
The primary objective of the current study is to investigate how internet use in the classroom in conjunction with metacognitive instruction affected students' metacognitive awareness, reading comprehension, and motivation. 40 pupils were randomly chosen from two eleventh-grade courses at Novin high school in Tabriz, Iran and split into two groups as follows: (a) experimental group called internet group – received metacognitive instruction along with the internet use; and (b) control group – received metacognitive teaching in a regular class. The findings indicate that although the students' motivation towards English study as a foreign language was significantly affected by the internet environment, their metacognitive awareness and reading comprehension were not affected. The results of the present study have some implications for syllabus designers, curriculum developers and language teachers.